Determination of the moisture content of soils with different densities by radioisotope methods - Zvolsky, S.T. (Reports of the National Academy of Sciences of Ukraine, 2014)
By calculations and experimentally, the additive component of the count rate of a neutron moisture meter, which is caused by the soil framework density, is identified. These data and the laboratory data on the bulk moisture and the soil framework density allow the construction of a single calibration curve for a neutron moisture meter in the entire interval of possible variations in the soil framework density. To interpret the results of borehole measurements with this curve, the soil framework density is replaced by the density of soil with a natural moisture, which was determined with a radioisotope density gage directly in a borehole under study.